Edukasi Gizi dan Distribusi Suplemen MMS Bagi Ibu Hamil: Studi Kasus di Puskesmas Banyudono II Kabupaten Boyolali - Dewiyanti Fitria; Agita Dianingsih; Dila Fatiha Sholiha; Hana Mamnukha; Budiyanti Wiboworini (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Introduction: Anemia in pregnant women remains a major maternal and child health problem, especially in rural areas. Providing Multiple Micronutrient Supplements (MMS) containing iron, folic acid, vitamin C, and zinc is an important intervention, but its implementation is often hampered by uneven distribution and a lack of understanding among pregnant women. Objective: This community service activity aimed to increase pregnant women's understanding of the importance of MMS consumption and ensure its optimal distribution in the Banyudono II Community Health Center area, Boyolali. In addition, data analysis assistance was provided to strengthen health workers' capacity in monitoring supplement distribution. Methods: The activity was carried out using descriptive methods and an observational approach. Data was obtained through documentation of counseling sessions, field observations, and MMS distribution records. Data analysis assistance was provided directly by the service team to community health center staff using a simple quantitative approach (frequency distribution). Results and Discussion: A total of 35.7% of pregnant women had received education and MMS, with the highest distribution found in the first trimester group (70%). The remaining women had not received it due to various reasons such as unsuitable gestational age, self-consumption of iron tablets, and absence from pregnant women's classes. Data assistance helped to identify these obstacles more precisely. Conclusion: This activity contributed to increasing pregnant women's nutritional literacy, strengthening data-driven MMS distribution systems, and bridging collaboration between educational institutions and primary healthcare services.